2019
DOI: 10.1038/s41416-018-0368-3
|View full text |Cite
|
Sign up to set email alerts
|

The physiological mTOR complex 1 inhibitor DDIT4 mediates therapy resistance in glioblastoma

Abstract: BACKGROUND: Despite significant advances in the understanding of glioblastoma genetics and biology, survival is still poor. Hypoxia and nutrient depletion in the tumour microenvironment induce adaptive signalling and metabolic responses, which can influence sensitivity to therapeutic regimens. DNA damage-inducible transcript 4 (DDIT4) is a protein induced by hypoxia and in response to DNA stress. Mechanistically, DDIT4 inhibits mammalian target of rapamycin complex 1 (mTORC1) signalling by activation of the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…With demeclocycline treatment in three BTIC lines (Figure 4C). Notably, a recent study has identified that temozolomide and radiotherapy could induce DDIT4 and repressed mTORC1 activity in some glioblastoma cell lines (44). Thus, overexpression of DDIT4 by demeclocycline in BTIC could be beneficial for glioblastoma patients.…”
Section: Mechanisms Of Demeclocycline-mediated Btic Growth Reductionmentioning
confidence: 99%
“…With demeclocycline treatment in three BTIC lines (Figure 4C). Notably, a recent study has identified that temozolomide and radiotherapy could induce DDIT4 and repressed mTORC1 activity in some glioblastoma cell lines (44). Thus, overexpression of DDIT4 by demeclocycline in BTIC could be beneficial for glioblastoma patients.…”
Section: Mechanisms Of Demeclocycline-mediated Btic Growth Reductionmentioning
confidence: 99%
“…mTORC1 multiprotein complex constitutes a major regulator of cell growth, translation, and metabolism, and has also been shown to inhibit autophagy [58,59]. Interestingly, over-expression of REDD1 in GB has been associated with resistance to temozolomide, radiotherapy, and resistance to hypoxia induced cell death, as well as linked to patient poor prognosis [60,61]. Nevertheless, the molecular mechanism(s) by which REDD1 promotes GB progression are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…As we better understand the molecular mechanisms underlying glioma development, molecular targeted therapy has been proposed as a promising treatment for glioma. For instance, BRAF [35], EGFR [36], EZH2 [37], MET [38] and mTOR [39] have been reported as potential protein targets for glioma treatment. However, because of the complexity of the occurrence and development of glioma, none of these targets can completely cure glioma; thus, more novel therapeutic targets are urgently needed.…”
Section: Discussionmentioning
confidence: 99%